The impacts of the lack of ergonomic vision in mining equipment design projects on the health of workers in the maintenance sector (Research, Society and Development, 2021)
This study aims to analyze the impacts of the lack of ergonomic view in the projects of equipment design on workers’ health from the maintenance sector, in the mining industry context. To understand the operators’ health, maintenance activities of three types of equipment were analyzed: pump, crusher and sieve. The methodological strategy of Ergonomic Analysis of the Workplace (EWA) was used. Thus, changes in these activities are required, since some postures adopted for their performance were considered severe and with high risk. Bearing weight above the shoulders and uncomfortable positions are conditions resulted from failures in the equipment designs. To alleviate the problem, it is suggested the adoption of innovative tools or the creation of new supportive devices to improve working conditions of these maintenance professionals.